Analisis strukturalisme pada cerpen “Coretan Tangan Lelaki Buta” karya A Warits Rovi - Khasanah, Uswatun (Maliki Interdisciplinary Journal, 2024)
Short stories are one of the most widely used literary works. The short story Scribbled Hands of a Blind Man was formed coherently by A Warits Rovi, so that it has coherence and a connection between one element and another. There are many ways to find out the contents of a literary work. One of them, as used by the author, is through structuralism studies. From this study, we can find out what is in this short story starting from theme, plot, setting, point of view, characters and characterization.